2010
DOI: 10.1007/s00436-010-2179-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple recombinant antigens of Clonorchis sinensis for serodiagnosis of human clonorchiasis

Abstract: Antigenic proteins from Clonorchis sinensis have been previously purified and evaluated for their antigenicity to enable the serodiagnosis of clonorchiasis. Though they were of high specificity, molecularly defined proteins were reported to be less sensitive as single antigens than crude antigen. To resolve this issue, 11 clones were selected by immunoscreening an adult C. sinensis cDNA library using infected human sera. Mixed antigens were prepared using recombinant proteins of positive clones and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
12
0
2
Order By: Relevance
“…[16][17][18] In serodiagnosis of human clonorchiasis, ELISA and/or immunoblotting has also been performed using somatic antigens produced from adult C. sinensis 19,20 and recombinant C. sinensis antigen. [21][22][23][24] In general, these methods are time consuming and cannot be used at patient contact. Here, we report the development and testing of a rapid diagnostic immunochromatographic test (ICT) for serodiagnosis of human opisthorchiasis and clonorchiasis.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In serodiagnosis of human clonorchiasis, ELISA and/or immunoblotting has also been performed using somatic antigens produced from adult C. sinensis 19,20 and recombinant C. sinensis antigen. [21][22][23][24] In general, these methods are time consuming and cannot be used at patient contact. Here, we report the development and testing of a rapid diagnostic immunochromatographic test (ICT) for serodiagnosis of human opisthorchiasis and clonorchiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cocktailed antigens can be used to overcome the limitation. Recently, multiple mixed antigen of recombinant 28 and 26 kDa glutathione Stransferases and vitelline precursor protein showed elevated diagnostic sensitivity and specificity (Li et al 2011). Bacterially produced rCsTSP2EC2 showed specific reactivity with human clonorchiasis sera by immunoblot in this study.…”
Section: Discussionmentioning
confidence: 89%
“…However, an accurate and feasible diagnostic method for clonorchiasis is US that characterize clonorchiasis as diffuse, mild, uniform dilatation of the small peripheral intra-hepatic bile ducts without a focal obstructing lesion; the CT imaging of clonorchiasis is same as those observed by US [ 59 ]. Li et al [ 58 ] reported that the recombinant Cs26GST and Cs28GST proteins are specifi c serodiagnostic antigens for human clonorchiasis, because of their non-cross-reactivity to the sera of paragonimiasis, schistosomasis, or cysticercosis; thus, a mixed antigen of recombinant 28 and 26 kDa glutathion S-transferases, Cs28GST and Cs26GST (producing 76 % sensitivity and 95 % specifi city), can be considered an useful serodiagnostic reagent for human clonorchiasis. The C .…”
Section: Diagnosismentioning
confidence: 91%
“…The diagnosis of clonorchiasis is done by microscopic fi ndings of fecal eggs [ 58 ], which are oval (measuring 27-35 × 12-20 μm), with an operculum at the slender end and prominent shoulders; broad abopercular end with small spine-like structure [ 56 ]. However, an accurate and feasible diagnostic method for clonorchiasis is US that characterize clonorchiasis as diffuse, mild, uniform dilatation of the small peripheral intra-hepatic bile ducts without a focal obstructing lesion; the CT imaging of clonorchiasis is same as those observed by US [ 59 ].…”
Section: Diagnosismentioning
confidence: 99%